Tabayyun dalam Al-Qur'an sebagai Penanggulangan Disinformasi Data - Nabila, Qoriatun; Halim, Abdul (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This study aims to analyze the concept of tabayyun in the Quran as a countermeasure against data disinformation amidst the rapid development of information technology and social media which has made it easier to disseminate information. Data disinformation is the spread of false information intentionally created to mislead the public. This phenomenon requires an ethical foundation and norms in responding to information circulating in society. The main objective of this study is to examine the Quranic perspective on the importance of information validation and the application of the tabayyun concept in social interaction. By directly referring to the Quran in Q.S. An-Nisa verse ninety-four and Q.S. Al-Hujurat verse six, as well as referring to three cross-era Quranic commentaries, namely Tafsir Jami' al-Bayan by Ath-Thabari, Tafsir Fathul Qadir by Asy-Syaukani, and Tafsir Fi Zhilalil Qur'an by Sayyid Quthb, this research is expected to provide an alternative solution for society in filtering information amidst the rampant flow of disinformation. The method used in this research is library research with a thematic exegesis approach (maudhu'i). Data were analyzed using descriptive-analytical methods. The results show that the concept of tabayyun in the Quran not only carries the meaning of clarity and truth but also contains commands to verify, clarify, and exercise caution in receiving and disseminating information. The principles of tabayyun explained by these commentators are relevant to be used as a foundation for countering data disinformation, particularly in the context of communication and interaction in the digital era.